Interiors, Affect, and Use: How Does an Academic Library’s Learning Commons Support Students’ Needs? - DeFrain, Erica; Hong, Miyoung (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – This study sought to identify the learning needs, satisfaction levels, and preferences of students using an academic library’s learning commons. A particular focus was understanding whether the socio-collaborative environment facilitated by the learning commons was aligned with the institutional objectives of supporting intensive study and scholarly work.Methods – A mixed methods sequential explanatory study design was used, in which quantitative findings were supplemented by qualitative findings. Data for the study were drawn from 59 hours of observations documenting behaviors of 9,249 individuals, as well as survey responses from 302 students. Three semi-structured focus groups with 10 students were held to discuss and clarify findings.Results – Behavior mapping and survey data showed that students were largely satisfied with the learning commons and that it was considered a supportive environment for them to complete their stated tasks. Incongruity was observed between the learning commons’ intended and actual use; although 75% of spaces were designated for collaboration, 50% of survey respondents identified independent work as their primary task and 76% of individuals were observed working independently. In focus group discussions, students praised the space for its vibrant ambiance and facilitation of social connections, but acknowledged that more serious study required retreat into quieter spaces found elsewhere in the library.Conclusion – The learning commons is an important and desirable space for students, providing a safe and community-oriented environment that is located in the center of campus. While students deemed the atmosphere successful for fostering social relationships and creating an overall sense of belonging, care needs to be taken to maintain a proper balance between quiet and collaborative spaces. The methods used in this study underscore the importance of gathering data from multiple sources, offering guidance to other libraries seeking to create, re-envision, and assess their learning spaces.